Population & Housing census atlas of Ethiopia 2007 - International Food Policy Research Institute; Ethiopian Development Research Institute; Central Statistical Agency (International Food Policy Research Institute, 2010)
The Population and Housing Census Atlas of Ethiopia 2007 comprises maps presenting a wide-ranging collection of data for different administrative levels. The maps provide information on biophysical environment, demographic characteristics, socioeconomic indicators, migration trends, and housing characteristics. The atlas format provides spatially disaggregated information on living conditions and demographic makeup in rural and urban Ethiopia, allowing the user to explore the various indicators and geographical distribution. Each indicator, disaggregated at the *woreda* level, provides a more profound understanding of economic clustering, social and welfare characterizations, and environmental classifications across the country.